Broad Bean Mosaic Caused by Pea Mosaic Virus - FUDL-ALLAH, ABD EL-SHAFY A.; YOUNES, HOSNY A. (The Libyan Journal of Agriculture, 2023)
Various types of mosaic diseases affecting broad bean are wide spread in Tripoli. Results on symptomatology, host range, and physical properties showed that viral isolates under study were probably strains of pea mosaic virus. The virus was readily transmitted mechanically to Vicia faba, Pisum sativum, and Lathyrus odoratus. Thermal inactivation occured between 52 60 C. The longevity in vitro at room temperature (20- 24 C) was about 120 hr. The dilution end point was between 10-3 and 10 5. This is the first report to indicate that broad bean mosaic in The Socialist People’s Libyan Arab Jamahiriya (S.P.L.A.J.) could be caused by pea mosaic virus.